Twenty-Seven-Gauge Vitrectomy-Assisted Four-Point Scleral Fixation of Intraocular Lens in the Absence of Capsular Support. Issue 8 (August 2016) - Wang, Wei; Syed, Reema; Hadayer, Amir; Jusufbegovic, Denis; Schaal, Shlomit
Abstract : Supplemental Digital Content is Available in the Text.